Green growth, natural resources and sustainable development: Evidence from BRICS economies. (December 2022) - Xu, Jiaqi; Zhao, Jingfeng; She, Shengxiang; Liu, Wen
Abstract: Most economies are shifting towards green growth to lower climate change and environmental degradation issues. Yet the question prevails regarding the nexus of green growth and economic performance. This study investigates the impact of green growth, green innovation, natural resources, and renewable energy on the economic performance of the BRICS economies. This study employs second-generation panel data approaches covering the period from 1991 to 2014. Slope heterogeneity, cross-section dependence, and unit root test is used. All the variables possess a long-run equilibrium relationship. While the method of moments quantile regression asserted that green growth exhibits a heterogeneous impact on economic performance. Green innovation is found in a negative association, while renewable energy consumption and natural resources are the prominent factors of economic performance in the region. The results are robust as the mean group estimator validates the findings of the earlier estimator. This study suggests appropriate policies for green growth to stabilize its positive influence on economic performance, enhancement of renewable energy consumption, and optimal use of natural resource rents to encourage economic performance in the region. Highlights: Nexus of green growth, natural resources, and sustainable development is analyzed. The role of renewable energy consumption is investigated in economic performance. Method of moment quantile regression and mean group estimators are used. Green growth heterogeneously affects economic performance in BRICS economies. Natural resources and renewable energy significantly promote economic performance.